Characteristics of infant formula consumed in the first months of life and allergy in the EDEN mother-child cohort - Moufidath Adjibade; Lucille Vigneron; Rosalie Delvert; Karine Adel‐Patient; Amandine Divaret‐Chauveau; Isabella Annesi‐Maesano; Barbara Heude; Marie‐Aline Charles; Blandine deLauzon‐Guillain (Wiley, 2024)
Abstract The evidence regarding the association between infant formula (IF) composition and the prevention of allergy and respiratory diseases remains sparse and inconclusive. This study aimed to evaluate whether some IF characteristics were associated with the risk of allergy or respiratory diseases in childhood. Among 1243 formula‐fed children from the EDEN mother-child cohort, IF characteristics concerning long‐chain polyunsaturated fatty acids (LCPUFAs) enrichment, prebiotic/probiotic enrichment, and hydrolysis of proteins were identified from the ingredients list. Eczema, wheezing, food allergy, asthma, and allergic rhinitis up to age 8 years were prospectively collected and summarized into four allergic and respiratory multimorbidity clusters. Associations between 4‐month IF characteristics and risk of allergy or respiratory diseases were tested using logistic regressions adjusted on main confounders. The consumption of LCPUFA‐enriched formula was not linked to allergic and respiratory multimorbidity clusters, but to a lower risk of any allergy, eczema, and wheezing. Probiotic‐enriched formula consumption was associated with a lower risk of belonging to the 'Allergy without asthma' cluster (odds ratio [OR] [95% confidence interval, CI] = 0.63 [0.40-0.99]), and consumption of a formula enriched in Bifidobacterium lactis was associated with a lower risk of any allergy (OR [95% CI] = 0.59 [0.41-0.85]). Partially hydrolysed formula (pHF) consumption was associated with a higher risk of belonging to the 'Allergy without asthma' cluster (OR [95% CI] = 2.73 [1.65-4.51]). This study confirms the positive association between pHF consumption and the risk of allergy found in previous observational studies and suggests that consumption of LCPUFA‐enriched or probiotic‐enriched formula was associated with a lower risk of allergy.